Development of wearable real time monitoring system for hand tremor through wireless communication - Teoh, Xin Ni; Airul Sharizli, Abdullah; Mohd Shawal, Jadin (2021)
Tremor constitutes one of the most important symptoms of neurological disorders. Tremor is an involuntary, rhythmic muscle contraction leading to shaking movements in one or more parts of the body. A common movement disorder that most often affects the hands